Perancangan Aplikasi Chat Realtime sebagai Media Bercerita Berbasis Android - Haidar Shiddiqramzy; Eko Sediyono (KITA Institute, 2023)
Storytelling is one way for an individual to share feelings and emotions with others. By telling stories, a person can get validation for their feelings so they don't feel isolated. In this research, a system is created to share stories using a system built on the Android Operating System and will be in the form of a Chat application. The method used in this research is Waterfall method and uses black box testing for system testing. The Database that will support the system to be built is Firebase which is directly integrated with the system created. The result of this research is an Android application that can be used by anyone and anywhere.